2015
DOI: 10.1111/apha.12505
|View full text |Cite
|
Sign up to set email alerts
|

Flecainide exerts paradoxical effects on sodium currents and atrial arrhythmia in murine R yR2‐P2328S hearts

Abstract: AimsCardiac ryanodine receptor mutations are associated with catecholaminergic polymorphic ventricular tachycardia (CPVT), and some, including RyR2-P2328S, also predispose to atrial fibrillation. Recent work associates reduced atrial Nav1.5 currents in homozygous RyR2-P2328S (RyR2S/S) mice with slowed conduction and increased arrhythmogenicity. Yet clinically, and in murine models, the Nav1.5 blocker flecainide reduces ventricular arrhythmogenicity in CPVT. We aimed to determine whether, and how, flecainide in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 57 publications
4
54
0
Order By: Relevance
“…In parallel with the present findings, RyR2 ‐P2328S cardiomyocytes also demonstrated acutely reduced Na v 1.5 function . This was partially rescued by pharmacological interventions reducing RyR2‐mediated Ca 2+ release . These findings together suggest direct effects of altered cytosolic [Ca 2+ ] upon Nav1.5 function .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In parallel with the present findings, RyR2 ‐P2328S cardiomyocytes also demonstrated acutely reduced Na v 1.5 function . This was partially rescued by pharmacological interventions reducing RyR2‐mediated Ca 2+ release . These findings together suggest direct effects of altered cytosolic [Ca 2+ ] upon Nav1.5 function .…”
Section: Discussionsupporting
confidence: 89%
“…Ag/AgCl electrodes maintained electrical connections to the organ bath and pipette. Loose patch‐clamp experiments were performed as previously described . The pipette was lowered onto the membrane surface and gentle suction applied to allow seal formation around the patch of membrane.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes could be attributed to (a) chronically down‐regulated expression of Na v 1.5 channels, demonstrated in RyR2 ‐P2328S ventricles (Ning et al , ), and (b) acute actions of increased [Ca 2+ ] i upon Na v 1.5 channel function. Loose‐patch clamp recordings demonstrated reduced peak I Na in whole isolated RyR2 ‐P2328S compared with WT atria to extents comparable with those reported in Nav1.5 channel‐haploinsufficent Scn5a +/− hearts (King et al , ; Salvage et al , ) (Figure A, left traces). These conduction abnormalities could not be attributed to either fibrotic change or altered connexin expression.…”
Section: Paradoxical Effects Of Flecainide On Arrhythmic Substrate Prsupporting
confidence: 72%
“…Flecainide (1 μM) modified arrhythmic tendency and conduction velocity in RyR2 ‐P2328S hearts, in directions that paradoxically contrasted with its corresponding effects upon either WT and Scn5a +/− hearts. It exerted pro‐arrhythmic atrial and ventricular effects in Scn5a +/− and some WT hearts, although it produced consistently anti‐arrhythmic effects in RyR2‐ P2328S atria (Salvage et al , ). Multi‐electrode recording array studies demonstrated marked conduction slowing in RyR2‐ P2328S compared with WT atria.…”
Section: Paradoxical Effects Of Flecainide On Arrhythmic Substrate Prmentioning
confidence: 99%